Expression of denitrification enzymes in response to the dissolved oxygen level and respiratory substrate in continuous culture of Pseudomonas stutzeri. - Körner, H (1989)
The onset and cessation of the synthesis of denitrification enzymes of Pseudomonas stutzeri were investigated by using continuous culture and defined dissolved oxygen levels covering the full range of transition from air saturation to complete anaerobiosis. Expression of nitrate reductase, nitrite reductase (cytochrome cd1), and N2O reductase was controlled by discrete oxygen levels and by the nature of the nitrogenous oxide available for respiration. N2O reductase was synthesized constitutively at a low level; for enhanced expression, oxygen concentrations were required to decrease below 5 mg of O2 per liter. The threshold values for synthesis of nitrate reductase and cytochrome cd1 in the presence of nitrate were ca. 5 and ca. 2.5 mg of O2 per liter, respectively. With nitrous oxide as the respiratory substrate, nitrite reductase was again the most sensitive to oxygen concentration; however, thresholds for all denitrification enzymes shifted to lower oxygen levels. Whereas the presence of nitrate resulted in maximum expression and nearly uniform induction of all reductases, nitrite and nitrous oxide stimulated preferably the respective enzyme catalyzing reduction. In the absence of a nitrogenous oxide, anaerobiosis did not induce enzyme synthesis to any significant degree. The accumulation of nitrite seen during both the aerobic-anaerobic and anaerobic-aerobic transition phases was caused by the differences in onset or cessation of synthesis of nitrate and nitrite reductases and an inhibitory effect of nitrate on nitrite reduction.